SPATIAL AND TEMPORAL VARIABILITY OF FISH COMMUNITY BIOMASS IN COASTAL WATERS OF TANGERANG REGENCY, BANTEN - Nina Nurmalia Dewi; M Mukhlis Kamal; Yusli Wardiatno (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2016)
Coastal waters of Tangerang Regency has abundant in fish resource including pelagic, demersal, and reef fish. This study was conducted to assess fish biomass variability and of fish community structure in coastal waters of Tangerang Regency which can be used as a basis in determining alternatives for sustainable fish resource management. This research was conducted in June and August 2013 in three locations i.e., Kronjo, Cituis, and Tanjung Pasir. Primary data collected were fish weight per species. Fish biomass from each locations was obtained using swept area method using trawl. The results showed that Kronjo region contained the highest total average biomass of fish. Temporally, total ave-rage biomass of fish in August was higher than in June for Kronjo and Cituis. Meanwhile, the con-trary occurred in Tanjung Pasir. This conditions occurred due to the high current and high wave in August than in June. In general, biomass of planktivorous was dominant during the study indicating overfishing lead to fishing down the food web in the Coastal waters of Tangerang Regency. Keywords: biomass, coastal waters of Tangerang Regency, spatial and temporal variability, swept area, over fishing.